Two new species of the genus Galianthe (Rubiaceae) from Brazil - Elsa L. Cabral (Bonplandia, 2004)
Galianthe longisepala E. L. Cabral and Galianthe matogrossiana E. L. Cabral, new species from Brazil, are described and illustrated.